Flu as problem common to all mankind. Future directions for prevention and treatment of influenza - Korovaeva, I; Kuhar, D; Popova, N; Mikhaylenko, K; Zozulya, N (Annals of Mechnikov's Institute, 2020)
This article discusses the flu, as one of the most common infectious diseases affecting humanity throughout its history. The data on the structure of A influenza virus and its variability is given historical background for most famous of the pandemics, which inflicted irreparable damage to the population of the Earth, are shown the basic stages of the study for influenza virus. Are considered the types of variability of the A virus influenza, its ability to overcome interspecies barriers that form the basis of pathogen escape from the immune response. The article shows the promising areas of modern prevention and treatment of this disease.